(untitled) (Polis (Santiago), 2018)
The understanding of the present crisis of world capitalist system is of great analytical complexity: it attracts seven theoretical explanations channeled through three paradigmatic strands, expresses ten critic dimensions, faces four symptomatic paradoxes and raises six politically differentiated responses. In addition to examining the intricate debate, this article critically examines the crisis as a structural, systemic and civilizatory problem. In first instance, this is a crisis of valorization which involves a spiral of over-accumulation, the falling rate of profit and the breakdown of the dynamics of accumulation; but ultimately it represents a crisis of civilization. The centralized global accumulation, led by transnational capital and based on the exploitation of cheap labor, environmental devastation and financialization, shows its true limits. Yet big business seeks to restore the process of capital concentration, power, wealth and knowledge, disregarding that human life and social metabolism are threatened in many ways.